Investigations into the stability of growth factor induced-vasculature and the effects of synthetic biomaterials on heart remodelling after myocardial infarction - Dobner, Stephan (Department of Surgery, 2014)
This work was based on the hypothesis that optimization of growth factor delivery rate and duration, combined with a biomaterial scaffold, could lead to an improved strategy for therapeutic neovascularization. To test this hypothesis, a novel in vivo model system that allows for characterization of stability and mural cell investment of newly created vessels was designed.